1991
DOI: 10.1016/1010-7940(91)90112-w
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pleural effusion and post-traumatic subarachnoidal-pleural fistula

Abstract: Post-traumatic subarachnoidal-pleural fistulae are rare. We have found 22 cases in the literature. A patient who was successfully treated by thoracotomy 1 1/2 years after blunt thoracic trauma is presented. Myelography is the diagnostic test of choice and surgical closure is necessary in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The first case was reported in 1959 by Milloy, et al 33 A search of Medline records revealed that since that first publication 54 cases have been reported. Thirty-seven were secondary to traumatic injury, [1][2][3][5][6][7][8]11,14,15,17,[20][21][22][23][24]26,29,30,[32][33][34][35][36][37][38][39][40][41][42]44,[47][48][49][50][51][52]55 and 15 to surgery. 4,9,10,12,13,16,19,25,27,28,34,43,45,...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case was reported in 1959 by Milloy, et al 33 A search of Medline records revealed that since that first publication 54 cases have been reported. Thirty-seven were secondary to traumatic injury, [1][2][3][5][6][7][8]11,14,15,17,[20][21][22][23][24]26,29,30,[32][33][34][35][36][37][38][39][40][41][42]44,[47][48][49][50][51][52]55 and 15 to surgery. 4,9,10,12,13,16,19,25,27,28,34,43,45,...…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 6,11,13,14,53 have postulated that conservative therapy is suitable in most of the patients. However, other authors 15,19,26,48 have argued that surgical repair of the fistula is essential and that early intervention in these cases is rewarding. There are also other suggested treatment options.…”
Section: Treatment Strategiesmentioning
confidence: 99%